ANALYSIS OF CLAY MINERALS POTENTIAL AS RARE EARTH ELEMENTS BEARING MINERALS: CASE STUDY IN NANGA TAYAP, KETAPANG, WEST KALIMANTAN - Dwicahya Yan Sutardi, Bagust
Rare earth elements (REEs), which include the lanthanide series plus yttrium and scandium, are essential to many modern technologies. The global demand for these elements leads to increased exploration activities, particularly in regions like Indonesia, known for significant REE deposits. REEs are present in different types of deposits, including those of ion adsorption type found in weathered granite regions. Such deposits enrich REEs in clay minerals, primarily kaolinite and halloysite. Therefore, this study was conducted as a preliminary investigation to identify clay minerals as carriers of ion adsorption-type REEs in the Nanga Tayap District, Ketapang Regency, West Kalimantan. The research methodology incorporated petrographic analysis, X-ray diffraction (XRD), reflectance spectroscopy, and scanning electron microscopy energy-dispersive X-ray spectrometry (SEM-EDS). Petrographic analysis showed potential for granite as an REE bearer, evidenced by zircon presence in the samples' thin sections. XRD analysis confirmed the presence of kaolinite group minerals in the collected soil samples, corroborated further by reflectance spectroscopy. SEM-EDS analysis revealed the presence of REEs linked to the clay minerals through examination of the clay minerals' elemental composition. The study thus implies that in the Nanga Tayap District, Ketapang Regency, West Kalimantan, kaolinite clay minerals likely bind REE ions in the weathered granite zone.